THE INFLUENCE OF ORGANIZATIONAL CULTURE AND EMPLOYEE ENGAGEMENT TO JOB BURNOUT ON GENERATION Z WORKING AT E-COMMERCE - Tulusiani Widjanarko (BISMA: Jurnal Bisnis dan Manajemen, 2021)
Generation Z is currently entering the workforce and is the youngest generation, and most of them work in an e-commerce company. E-commerce is synonymous with competitive culture, and many demands to be independent and proactive in their work. That situation is a challenge for generation z, which if they cannot handle it properly, it will become a stress in itself, which over time can become burnout. This study aimed to determine the influence of organizational culture and employee engagement on job burnout and examine the factors that influence stress in the workplace. In this research, the approach method was used by distributing questionnaires filled out by 180 respondents who are Generation Z. The responses were analyzed using multiple linear regression. These results indicated a significant effect between employee engagement and job burnout. Meanwhile, the effect of organizational culture on job burnout was insignificant. This research also found that about 56% of the respondents experienced a moderate level of job burnout. Keywords: e-commerce, employee engagement, generation z, job burnout, organizational culture